2011
DOI: 10.1371/journal.pone.0027227
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol (4,5) Bisphosphate Controls T Cell Activation by Regulating T Cell Rigidity and Organization

Abstract: Here we investigate the role of Phosphatidylinositol (4,5) bisphosphate (PIP2) in the physiological activation of primary murine T cells by antigen presenting cells (APC) by addressing two principal challenges in PIP2 biology. First, PIP2 is a regulator of cytoskeletal dynamics and a substrate for second messenger generation. The relative importance of these two processes needs to be determined. Second, PIP2 is turned over by multiple biosynthetic and metabolizing enzymes. The joint effect of these enzymes on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 41 publications
5
32
0
Order By: Relevance
“…These data are consistent with work by Raucher et al 45,46 that demonstrated that marked disruption of PIP 2 by overexpression of phospholipidsequestering polypeptides or inositol phosphatases or by pharmacologic activation of phospholipase C reduces the adhesion energy between the cell membrane and the cytoskeleton. Our data also support the findings by Sun et al, 47 which showed that overexpression of PIP5KIg increased the rigidity of the membrane in T cells. The structural mediators of this PIP 2 -driven signal are less clear, but candidate PIP 2 -binding proteins are vinculin, talin, and filamin.…”
Section: Discussionsupporting
confidence: 93%
“…These data are consistent with work by Raucher et al 45,46 that demonstrated that marked disruption of PIP 2 by overexpression of phospholipidsequestering polypeptides or inositol phosphatases or by pharmacologic activation of phospholipase C reduces the adhesion energy between the cell membrane and the cytoskeleton. Our data also support the findings by Sun et al, 47 which showed that overexpression of PIP5KIg increased the rigidity of the membrane in T cells. The structural mediators of this PIP 2 -driven signal are less clear, but candidate PIP 2 -binding proteins are vinculin, talin, and filamin.…”
Section: Discussionsupporting
confidence: 93%
“…They remain detectable at the pSMAC of the mature synapse, possibly assisting the active vinculin conformation. PIPKIg is also found at the T cell synapse; the spatiotemporal regulation of PIP 2 synthesis appears to control T cell rigidity and signaling organization (42).…”
Section: Discussionmentioning
confidence: 99%
“…In T lymphocytes, PIP2 concentrates at the IS at a very early stage upon Ag recognition (43), and data obtained by overexpressing PIP5K isoforms in transgenic mice showed the enrichment of distinct isoforms at the IS (20).…”
Section: Discussionmentioning
confidence: 93%
“…Primary CD4 + T cells express all three PIP5K isoforms (a, b, and g), with a specific subcellular localization (19). Human PIP5Ka accumulates in a sustained manner in the T:APC contact zone (20), where it regulates CD28-mediated actin polymerization events necessary for CD28 costimulatory signaling (21,22). PIP5Kg90 is predominantly found at the distal pole and in the uropod.…”
Section: P Hosphatidylinositol 45-biphosphate (Pip2) Represents 1%mentioning
confidence: 99%
See 1 more Smart Citation